2019
DOI: 10.1177/0967391119852882
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of jute fiber–reinforced UP/PU hybrid network composites

Abstract: Hybrid networks (unsaturated polyester–polyurethane (UP/PU)) of UP resin and PU prepolymer were synthesized and characterized for their phase miscibility with the help of Fourier transform infrared spectroscopy, differential scanning calorimetry, dynamic mechanical analysis (DMA), and atomic force microscopy. The existence of hydrogen bonded –NH groups, broadened glass transition region, and reduced phase domains evidenced the formation of intermixed phase when compared with the parent UP. The optimum mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…The particles act as active points, and reduce the polymer chain mobility, limiting cells' formation and growth [31,36]. These interactions increased the interpenetration of the three phases and formed many cells with small sizes [8], as presented in Figure 2 and Figure 4, which shows a schematic representation of possible interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particles act as active points, and reduce the polymer chain mobility, limiting cells' formation and growth [31,36]. These interactions increased the interpenetration of the three phases and formed many cells with small sizes [8], as presented in Figure 2 and Figure 4, which shows a schematic representation of possible interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Different polymers are used as matrix materials for composite preparation, depending on their applications [4–6]. Polyurethane (PU) foams are materials with a stiffened polymeric structure, whose variation in density or pore size allows a wide range of applications, such as high‐performance adhesives, sealants, paints, seals, and also more noble applications, such as removing contaminants in air and water and absorption of spilled oil [7–10].…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen from Table S2 that the elastic modulus and tensile properties showed the same trend, which may be because the BC powder acted to connect the macromolecules inside the PU when the foam was subjected to external force, thereby increasing the strength of the foam. However, when the BC content was too high, agglomeration would occur during the synthesis of PU, which would affect the gel reaction, resulting in the inability to find effective connections between polymers, and some hollow bottom droplets may appear, resulting in declining of mechanical properties (Singh et al 2019). The results revealed that the mechanical properties of BC/PU foam were improved effectively after adding less BC powder, which provides an effective basis for the application in other fields.…”
Section: Mechanical Property Of Bc/pu Foam Compositesmentioning
confidence: 95%
“…The synthesis of polyurethane prepolymer was carried out using polyether polyol and MDI (1:2 molar ratio) in a resin kettle at 80°C for 2 h under a nitrogen atmosphere as described earlier. 32 The resulting prepolymer was blended with vinylester resin at different NCO/OH ratios. The blends were thoroughly stirred and degassed for ∼3 min.…”
Section: Methodsmentioning
confidence: 99%